Finding our way : leadership for an uncertain time - Wheatley, Margaret J. (Berrett-Koehler Publishers, 2007)
Provocative, challenging, at times poetic, and often deeply moving, Finding Our Way touches on all the topics Wheatley has addressed throughout her illustrious career, showing how she has applied the ideas in her books in many different situations.